2013
DOI: 10.1021/nn401657n
|View full text |Cite
|
Sign up to set email alerts
|

Nonmonotonic Size Dependence in the Hole Mobility of Methoxide-Stabilized PbSe Quantum Dot Solids

Abstract: We present a facile procedure to fabricate p-type PbSe-based quantum dot solids with mobilities as large as 0.3 cm2 V–1 s–1. Upon partial ligand exchange of oleate-capped PbSe quantum dots with the methoxide ion, we observe a pronounced red shift in the excitonic transition in conjunction with a large increase in conductivity. We show that there is little correlation between these two phenomena and that the electronic coupling energy in PbSe quantum dot solids is much smaller than often assumed. However, we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 37 publications
1
48
1
Order By: Relevance
“…In a recent study of lead chalcogenide nanoparticles capped with the methoxide ion, no significant changes in the carrier concentration was found upon varying the nanoparticle diameter between 3.0 and 8.9 nm. 67 We therefore assume the carrier concentrations of the two PbS particle samples capped with MeO − used in this work to be of similar magnitude. In Figure 4, the Ar binding energies in the near surface region of the four PbS samples studied here are shown.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…In a recent study of lead chalcogenide nanoparticles capped with the methoxide ion, no significant changes in the carrier concentration was found upon varying the nanoparticle diameter between 3.0 and 8.9 nm. 67 We therefore assume the carrier concentrations of the two PbS particle samples capped with MeO − used in this work to be of similar magnitude. In Figure 4, the Ar binding energies in the near surface region of the four PbS samples studied here are shown.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] The inherent large surface-to-volume ratio of QD materials results in unsaturated dangling bonds, creating undesired electronic trap states within the bandgap of QD solids. The ligand exchange procedure itself is prone to create new, rather than passivate existing, dangling bonds.…”
mentioning
confidence: 99%
“…34 Since the optoelectronic properties of PbS NC ensembles bear many opportunities for applications in solar cells or photodetectors, a number of ligand exchange procedures with small organic or inorganic molecules as well as single atom passivation strategies have been developed, all of which greatly increase the carrier mobilities within the SL of NCs. 28,33,[35][36][37][38][39][40][41][42][43][44] Due to the short interparticle spacing imposed by these ligands, structural coherence is mostly lost in such superlattices, but in rare cases it has been demonstrated that significant long-range order and even mesocrystallinity can be preserved. 25,35,45 However, a persisting problem of these protocols is that they are prone to introduce defects in the superlattice structure with some degree of granularity and significantly smaller grain sizes, which poses difficulties in determining the angular correlation with a meaningful statistical distribution.…”
mentioning
confidence: 99%